Parques científicos y tecnológicos: de la planificación a la evaluación - José Luis Sánchez Hernández (Anales de Geografía de la Universidad Complutense, 2004)
Filteen years after their settlement in Spain, it comes to a necessity to assess the outcomes of science & technology parks. This article launches an assessment methodology that stems from the main goals of these modern infrastructures: production of a top-level urban quartier, recovery the invested funds and resources, fostering of research and cooperation networks, creation of a techno-scientific node and contribution to technological and economic regional development. This methodology does not limit to measure neither the activity of the park nor its current or ordinary influence, but is an effort to support its management, to improve its strenght and to erase its weaknessess. Therefore, promoting institutions and public bodies should be responsible for testing this evaluation protocol.